Spraying materials and spraying methods

A spraying material and method using blast furnace slag and fly ash with specific additives address high pH issues, reducing Si ion elution and ensuring rapid strength development for construction and waste disposal applications.

JP7620435B2Active Publication Date: 2025-01-23DENKA CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021008600
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-22
Publication Date
2025-01-23
Estimated Expiration
2041-01-22

AI Technical Summary

Technical Problem

Existing spraying methods for concrete in construction and radioactive waste disposal sites face challenges with high pH levels, leading to issues like groundwater infiltration and reduced hydraulic conductivity, and the elution of Si ions, which affect the strength and durability of the sprayed materials.

Method used

A spraying material composed of blast furnace slag-containing cement, fly ash, a high-strength admixture, quick-setting agent, fine and coarse aggregates, and specific additives like alkali metal carbonate and oxycarboxylic acids, along with a spraying method that involves dry mixing and kneading, ensures low pH and reduced Si ion elution while maintaining initial strength.

Benefits of technology

The solution effectively reduces Si ion elution and maintains low pH, ensuring rapid strength development and improved durability of the sprayed materials, preventing groundwater infiltration and enhancing the structural integrity of construction sites and radioactive waste containment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620435000001
    Figure 0007620435000001
  • Figure 0007620435000002
    Figure 0007620435000002
  • Figure 0007620435000003
    Figure 0007620435000003
Patent Text Reader

Abstract

To provide a spray material and a spraying method that enable the elution amount of Si ions to be reduced and the pH is lowered in comparison with the conventional technology while ensuring the initial strength after spraying.SOLUTION: A spray material includes a cement material comprising blast furnace slag having cement and fly ash, a high-strength admixture, a quick binder, a fine aggregate, a coarse aggregate and water. The high-strength admixture includes gypsum, 0.5-5 pts.mass of alkali metal carbonate per 100 pts.mass of gypsum calculated on the basis of CaSO4 and 0.2-5 pts.mass of oxycarbonic acids per 100 pts.mass of gypsum calculated on the basis of CaSO4. The quick binder includes calcium aluminate, 1-20 pts.mass of alum on the basis of 100 pts.mass of calcium aluminate and 1-20 pts.mass of calcium hydroxide on the basis of 100 pts.mass of calcium aluminate. The content of the fly ash is 30-400 pts.mass per 100 pts.mass of cement containing blast furnace slag. The content of the high-strength admixture is 6-20 pts.mass per 100 pts.mass of the cement material. The content of the quick binder is 6-20 pts.mass per 100 pts.mass of the cement material. The water content is 30-55 pts.mass per 100 pts.mass of the cement material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spraying material that can provide support for exposed ground in a short period of time and achieve a low pH in the construction of underground cavities, for example, tunnels for roads, railways, and water conduits, and underground cavities, such as oil or LNG storage facilities and radioactive waste disposal sites, and a spraying method using the same. [Background technology]

[0002] As a spraying method that shows strength development in a short time, a spraying method using a combination of cement, calcium aluminate, and gypsum has been proposed (Patent Documents 1 to 4). However, it has been technically difficult to achieve a low pH for concrete sprayed using these methods. The reason for this is that the ability to show strength development in a short time is determined by the amount of calcium hydroxide generated after the cement-based material hardens, and when short-term strength is to be developed, ordinary cement or high-early-strength cement, which produces a large amount of calcium hydroxide, is used.

[0003] Also, a cement-based material for radioactive waste disposal sites that combines cement, fly ash, and silica fume has been proposed (Patent Document 5). However, Patent Document 5 is related to cement-based materials for radioactive waste disposal sites, and does not describe spraying materials or spraying methods. In addition, when these are used for spraying, the strength of the material reaches 3N / mm within 10 minutes. 2 It was not possible to obtain a compressive strength of the above.

[0004] In addition, in places like Japan where there are many cracks in the rock, spring water may occur through the sprayed concrete after tunnel excavation for roads or railway tunnels. In such cases, highly alkaline components are eluted from the sprayed concrete, so work is carried out to treat the resulting spring water and lower its pH level. When such sprayed materials are used as support materials in the construction of radioactive waste disposal sites, the infiltration of high pH groundwater becomes an issue. Currently, the method of radioactive waste disposal involves forming underground caverns as disposal facilities for radioactive waste discharged from nuclear power generation, and storing it for a long period of time.In this case, rather than storing the radioactive waste as it is, it is planned to fill the space between the bedrock and the container containing the radioactive waste. As such a filler, clay minerals such as bentonite, which are mineral-based and have swelling properties, have been considered (Non-Patent Document 1). However, it has been reported that even if the space between the bedrock and the waste container is filled with bentonite clay minerals, they can be altered depending on the pH of the water they come into contact with, causing their permeability to change, and that when they come into contact with groundwater with a pH of 12 or higher, the permeability increases and the water-stopping effect is weakened, making the low pH of sprayed concrete an issue.

[0005] Furthermore, it has been proposed to use a blended cement using ordinary cement, fly ash, and silica fume (Non-Patent Document 2). However, with this blended cement, the pozzolanic reaction does not proceed because the silica fume used contains little irritating components, and when immersed in spring water or still water, silicon ions caused by the silica fume dissolve and create voids, which is an issue. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-001203 A [Patent Document 2] JP 2007-297227 A [Patent Document 3] Japanese Patent Application Publication No. 09-169557 [Patent Document 4] Re-special publication WO01 / 060760 publication [Patent Document 5] JP 2000-065992 A [Non-patent literature]

[0007] [Non-Patent Document 1] Alteration behavior of bentonite-based materials by alkaline solutions in radioactive waste disposal (part 1) -Mineralogical alteration and permeability change of compacted bentonite immersed in various alkaline solutions-Central Research Institute of the Electric Power Industry Report of the Central Research Institute of the Electric Power Industry Research Report: N09015 May 2010 [Non-Patent Document 2] Hiroshi Uchikawa, Effect of admixtures on hydration and structure formation of blended cement, Part 4, Cement & Concrete, No. 488, October 1987 Summary of the Invention [Problem to be solved by the invention]

[0008] In view of the above problems, the present invention aims to provide a spraying material and a spraying method that can reduce the amount of Si ion elution compared to conventional techniques while ensuring the initial strength after spraying, and can achieve a low pH. [Means for solving the problem]

[0009] The inventors of the present invention have conducted extensive research to solve the above problems, and have confirmed that by using a specific material, it is possible to reduce the amount of eluted Si ions compared to the conventional technology and achieve a low pH while still ensuring the initial strength after spraying. This has led to the completion of the present invention. [1] A spraying material comprising a cement material consisting of blast furnace slag-containing cement and fly ash, a high-strength admixture, an accelerator, fine aggregate, coarse aggregate, and water, wherein the high-strength admixture comprises gypsum, 0.5 to 5 parts by mass of an alkali metal carbonate per 100 parts by mass of the gypsum converted into CaSO4, and 0.2 to 5 parts by mass of an oxycarboxylic acid per 100 parts by mass of the gypsum converted into CaSO4, and the accelerator comprises calcium aluminate and 1 to 20 parts by mass of alum per 100 parts by mass of the calcium aluminate. A spraying material comprising: a bun; and 1 to 20 parts by mass of calcium hydroxide per 100 parts by mass of the calcium aluminate; the fly ash content is 30 to 400 parts by mass per 100 parts by mass of the blast furnace slag-containing cement; the high-strength admixture content is 6 to 20 parts by mass per 100 parts by mass of the cement substance; the quick-setting admixture content is 6 to 20 parts by mass per 100 parts by mass of the cement substance; and the water content is 30 to 55 parts by mass per 100 parts by mass of the cement substance. [2] The spraying material according to [1], wherein the blast furnace slag is present in an amount of 5 to 250 parts by mass per 100 parts by mass of the cement. [3] A spraying method using the spray material described in [1] or [2]. [4] A spraying method as described in [3], in which a cement material consisting of blast furnace slag-containing cement and fly ash, fine aggregate, and coarse aggregate are dry mixed, water is then added and the mixture is kneaded, a high-strength admixture is then added, and a quick-setting agent is further added to prepare quick-setting sprayed concrete, which is then sprayed. Effect of the Invention

[0010] According to the present invention, it is possible to provide a spraying material and a spraying method that can reduce the amount of Si ion elution compared to conventional techniques while ensuring the initial strength after spraying, and can achieve a low pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. In the present invention, parts and percentages are based on mass unless otherwise specified. Moreover, the spraying material of the present invention refers to a material that does not contain aggregate or a material that contains aggregate.

[0012] In the present invention, cement containing blast furnace slag is used to impart strength development to the sprayed concrete and to reduce calcium hydroxide produced after hardening. The blast furnace slag-containing cement used in the present invention is preferably, but not limited to, the commonly used blast furnace cement types A, B, and C described in JIS R 5211. It is also possible to use a mixture of ordinary Portland cement and blast furnace slag. The Blaine specific surface area value (hereinafter referred to as the Blaine value) of blast furnace slag-containing cement is 2,500 to 10,000 cm 2 / g is preferred, and 3,500 to 6,500 cm 2 / g is more preferable. 2 If it is less than 10,000 cm / g, the initial strength of the sprayed concrete may be impaired. 2 If it exceeds this value, the concrete may become viscous and its pumpability may be impaired.

[0013] The blast furnace slag used here is, for example, granulated blast furnace slag consisting of 41-44% CaO, 13-16% Al2O3, and 32-36% SiO2, and it is difficult to use converter slag, electric furnace slag, and slowly cooled slag. The Blaine value of blast furnace slag is 2,500 to 10,000 cm 2 / g is preferred, and 3,500 to 6,500 cm 2 / g is more preferable. 2 / g or more, excellent early strength development of the shotcrete is obtained, and the initial strength of 10,000 cm 2 By ensuring that the viscosity of the concrete is not more than 1 / g, the viscosity of the concrete can be suppressed and pumpability can be improved. The content of blast furnace slag is preferably 5 to 250 parts, more preferably 50 to 150 parts, per 100 parts of cement. When the content is 5 parts or more, the pH of the resulting hardened cement body can be adjusted to 11 or less, and when the content is 250 parts or less, excellent early strength development can be obtained.

[0014] In the present invention, fly ash is used to consume calcium hydroxide that is produced due to the blast furnace slag-containing cement after hardening. Furthermore, fly ash also reacts with calcium hydroxide contained in the quick-setting admixture, and therefore consumes calcium hydroxide that is not consumed in the reaction of the quick-setting admixture. The fly ash used in the present invention is preferably fly ash for concrete, type I, type II, type III, or type IV, as described in JIS A 6201, but is not particularly limited. The Blaine value of fly ash is 2,500 to 10,000 cm 2 / g is preferred, and 3,500 to 6,500 cm 2 / g is more preferable. 2 / g or more, excellent early strength development of the shotcrete is obtained, and the initial strength of 10,000 cm 2 By ensuring that the viscosity of the concrete is not more than 1 / g, the viscosity of the concrete can be suppressed and pumpability can be improved. The amount of fly ash used in the present invention is 30 to 400 parts per 100 parts of blast furnace slag-containing cement. If it is less than 30 parts, the pH after hardening may not decrease, and if it exceeds 400 parts, the initial strength of the sprayed concrete may be impaired. The amount of fly ash is preferably 80 to 300 parts, more preferably 100 to 250 parts, per 100 parts of blast furnace slag-containing cement.

[0015] The unit amount of the cement material consisting of the blast furnace slag-containing cement and fly ash of the present invention is 360 to 600 kg / m 3 is preferable, and 400 to 550 kg / m 3 More preferably, 360 kg / m 3 By setting the concrete strength at 600kg / m or more, the concrete can be prevented from separating out and workability can be improved.3 By satisfying this condition, the viscosity of the concrete can be suppressed and construction workability can be improved.

[0016] The amount of water in the present invention is 30 to 55 parts per 100 parts of the cement material consisting of blast furnace slag-containing cement and fly ash. If it is less than 30 parts, there is a risk of the pipe being clogged during spraying, and if it is more than 55 parts, there is a risk of the desired compressive strength not being obtained. The amount of water is preferably 35 to 45 parts, more preferably 37 to 43 parts, per 100 parts of the cement material.

[0017] The high-strength admixture used in the present invention is used for the purpose of improving the strength development of the hardened cement body, and contains gypsum as a main component. Examples of gypsum include anhydrous gypsum, hemihydrate gypsum, and dihydrate gypsum, and one or more of these can be used. The crystal form of gypsum is not particularly limited, and α-type hemihydrate gypsum, β-type hemihydrate gypsum, type I anhydrous gypsum, type II anhydrous gypsum, type III anhydrous gypsum, and the like can be used. The gypsum includes naturally occurring gypsum, and waste gypsum and anhydrous gypsum obtained as an industrial by-product. The grain size of the gypsum is 2,000 cm in Blaine value. 2 / g or more is preferable, and 3,000 cm 2 / g or more is more preferable from the viewpoint of strength development.

[0018] The alkali metal carbonate used in the present invention improves the initial strength. Examples of the alkali metal carbonate include sodium carbonate, potassium carbonate, and sodium bicarbonate. One or more of these can be used. The content of the alkali metal carbonate is 0.5 to 5 parts per 100 parts of gypsum converted into CaSO4. If it is less than 0.5 parts, there is no effect, and if it exceeds 5 parts, the slump retention of the concrete decreases, and the workability tends to deteriorate. The content of the alkali metal carbonate is preferably 1 to 4.5 parts, more preferably 1 to 4 parts, per 100 parts of gypsum converted into CaSO4.

[0019] The hydroxycarboxylic acids used in the present invention improve the initial strength. Examples of oxycarboxylic acids include gluconic acid, tartaric acid, citric acid, malic acid, salicylic acid, and lactic acid, or salts thereof. Of these, citric acid is preferred. The content of the oxycarboxylic acid is 0.2 to 5 parts per 100 parts of gypsum converted into CaSO4. If it is less than 0.2 parts, the setting property and early strength development of the spraying material are inhibited, and if it exceeds 5 parts, the setting property and strength development may be inhibited. The content of the oxycarboxylic acid is preferably 1 to 4.5 parts, more preferably 1 to 4 parts, per 100 parts of gypsum converted into CaSO4.

[0020] The content of the high-strength admixture is 6 to 20 parts per 100 parts of the cement material consisting of blast furnace slag-containing cement and fly ash. If it is less than 6 parts, the initial strength may not be obtained, and if it exceeds 20 parts, the concrete may expand over a long period of time, which may impair the strength development. The content of the high-strength admixture is preferably 7 to 18 parts, more preferably 8 to 16 parts, per 100 parts of the cement material.

[0021] The calcium aluminate used in the present invention is a quick-setting component that causes early setting of cement concrete. Calcium aluminate is a calcium aluminate containing CaO and Al2O3 as main components and containing 1 to 4 parts of SiO2 in terms of oxide, which is obtained by mixing a raw material containing calcia, a raw material containing alumina, a raw material containing silica, etc., and performing heat treatment such as firing in a kiln or melting in an electric furnace. In addition, a compound in which a part of CaO and / or Al2O3 of calcium aluminate is replaced with an alkali metal oxide, an alkaline earth metal oxide, titanium oxide, iron oxide, an alkali metal halide, an alkaline earth metal halide, an alkali metal sulfate, an alkaline earth metal sulfate, etc., or a substance in which a small amount of these are dissolved in a substance containing CaO and Al2O3 as main components can also be used. The mineral form may be either crystalline or amorphous. Among these, amorphous calcium aluminate is preferred in terms of reaction activity and pumpability. 12 Amorphous calcium aluminate obtained by quenching a heat-treated product containing a portion of silicon oxide in the A7 composition is more preferable. The amount of SiO2 contained in calcium aluminate is preferably 1 to 4 parts, more preferably 2 to 4 parts, calculated as oxide, per 100 parts of calcium aluminate. When the amount is 1 part or more, good setting characteristics are exhibited, and when the amount is 4 parts or less, early strength is obtained. The particle size of calcium aluminate is 5,000 cm in Blaine value. 2 / g or more is preferable. 2 / g or more, the quick-setting property and the early strength development can be improved.

[0022] The alums of the present invention are used for the purpose of promoting initial setting and are effective in promoting strength development. Examples of alums include potassium aluminum sulfate, ammonium aluminum sulfate, and alumite such as potassium alumite, aluminum alumite, and ferric alumite. These usually contain water of crystallization, but products obtained by heating these at 50 to 600° C. and calcining them can also be used. The content of the alums is 1 to 20 parts relative to 100 parts of calcium aluminate. If it is less than 1 part, there is a risk of inhibiting initial setting, and if it exceeds 20 parts, it is likely to reduce setting properties and inhibit long-term strength development. The content of the alums is preferably 1.5 to 15 parts, more preferably 2 to 10 parts, relative to 100 parts of calcium aluminate. The particle size of alum is 400 to 1000 cm in Blaine value. 2 / g, and 600 to 800 cm 2 / g. 2 / g, rapid setting properties and long-term strength development can be ensured, and good early strength development can be easily obtained.

[0023] The calcium hydroxide of the present invention is used, for example, for the purpose of promoting early strength development. Examples of calcium hydroxide include commercially available hydrated lime and carbide slag produced as a by-product when acetylene is generated from calcium carbide. The content of calcium hydroxide is 1 to 20 parts per 100 parts of calcium aluminate. If it is less than 1 part, there is a risk of inhibiting initial setting, and if it exceeds 20 parts, it is likely to cause a decrease in setting property and inhibit long-term strength development. The content of calcium hydroxide is preferably 1.5 to 15 parts, more preferably 2 to 10 parts, per 100 parts of calcium aluminate.

[0024] The content of the quick-setting admixture mainly composed of calcium aluminate, alums, and calcium hydroxide is 6 to 20 parts per 100 parts of the cement material consisting of blast furnace slag-containing cement and fly ash, from the viewpoints of workability, early strength development, and durability. If it is less than 6 parts, the setting force and strength development may decrease, and if it exceeds 20 parts, the shotcrete may clog pipes during spraying or may impair long-term strength development. The content of the quick-setting admixture is preferably 7 to 18 parts, more preferably 8 to 16 parts, per 100 parts of the cement material.

[0025] In the present invention, if necessary, commercially available cement admixtures (materials) such as water reducing agents, air entraining agents, polymer emulsions, thickening agents, shrinkage reducing agents, rust inhibitors, antifreeze agents, clay minerals, and silica fume may be used to the extent that they do not impair performance.

[0026] The fine aggregate and coarse aggregate used in the present invention preferably have a low water absorption rate and high strength per se, but are not particularly limited thereto. The fine aggregate is preferably one having a maximum dimension of 5 mm or less, and examples of the fine aggregate include river sand, mountain sand, crushed stone, etc. The coarse aggregate is preferably one having a maximum dimension of 15 mm or less. The ratio of fine aggregate to coarse aggregate can be expressed by the ratio of the volume (s) of fine aggregate to the volume (a) of aggregate, and s / a is preferably 60 to 70 volume %.

[0027] In the present invention, the method for producing the shotcrete is not particularly limited as long as the gypsum is mixed in the shotcrete before mixing with the quick-setting agent. There are a method in which a specified amount of gypsum is mixed in the cement in advance, a method in which gypsum is added separately when the shotcrete is mixed, and the like.

[0028] As the mixing device, any existing device can be used, for example, a tilting mixer, an omni mixer, a Henschel mixer, a V-type mixer, a Nauta mixer, and the like.

[0029] The spraying method of the present invention can be carried out by a generally applicable wet spraying method or the like, in which concrete manufactured by mixing specified materials is pumped by a concrete pump through a sprayed concrete pumping pipe, and a mixing pipe such as a Y-shaped pipe is installed just before the spraying nozzle while the sprayed concrete is being pumped, and the concrete is mixed with a powdered quick-setting agent that has been pumped separately, and the resulting quick-setting sprayed concrete is sprayed onto the natural ground.

[0030] As a pipe for pumping concrete, a pressure-resistant metal mesh hose (pressure-resistant hose) or metal piping can be used. Usually, a pressure-resistant hose is used, and it is preferable to use metal pipes before and after it.

[0031] There is no particular limit to the length of the pressure-resistant hose, and the length used varies depending on the construction situation, but a length of 5 to 30 m is usually used. The diameter of the pressure-resistant hose is usually 2.5 to 3.5 inches from the viewpoints of pumpability and ease of handling.

[0032] The nozzle used in the present invention may be one that is continuously tapered or one that has a straight pipe attached to straighten the quick-setting shotcrete after tapering. The length of the quick-setting admixture mixing section is preferably about 15 to 145 cm, and more preferably 25 to 75 cm, from the viewpoints of mixability, adhesion, and pumpability of the shotcrete and the quick-setting admixture. The nozzles that can be used are made of metal or ceramic, and the inner surface of the nozzle pipe made of rubber material can be lined with ceramic or metal, or have chips of these embedded in it.

[0033] In the present invention, conventional spraying methods can be used, the spraying pressure is not particularly limited, and the discharge amount of sprayed concrete is usually 1.5 to 20 m 3 / h, and the amount of blown air is not particularly limited.

[0034] The spraying equipment is not particularly limited as long as it can spray sufficiently. For example, Ariva Corporation's product name "Ariva 280", Shintech Corporation's "MKW-25SMT", PET Corporation's "G4 Pump", as well as squeeze pumps, plunger pumps, diaphragm pumps, screw pumps, and gear pumps can be used to pump the sprayed concrete. EXAMPLES

[0035] The present invention will be described in more detail below based on experimental examples, but the present invention is not limited to these.

[0036] [Experimental Example 1] In order to evaluate the 10-minute strength development and pH, a spraying test was conducted focusing on the powder composition of the sprayed concrete. Using the materials shown below, the unit amount of cement material consisting of blast furnace slag cement and fly ash is 500 kg / m 3 A base concrete was prepared by mixing a mix with a fine aggregate ratio (s / a) of 65%, 45 parts water per 100 parts cementitious material, and 12 parts of high-strength admixture consisting of 3 parts oxycarboxylic acid and 3 parts alkali metal carbonate per 100 parts cementitious material converted into CaSO4, with the result that the base concrete was prepared as sprayed concrete and pumped using a concrete pump "Syntech MKW-25MT". 100 parts of calcium aluminate, 10 parts of alums, and 3 parts of calcium hydroxide were mixed to prepare quick-setting agent A, and a Y-shaped pipe was provided midway through the pressure delivery pipe, making the mixing section 100 cm long. The powdered quick-setting agent was pneumatically pumped using the "Denkanatomcrete PAC250V" powdered quick-setting agent adding device, and 12 parts were added to 100 parts of cement material to make a quick-setting sprayed cement concrete. The compressive strength was measured at 10 minutes and 3 hours. At each test, the quick-setting shotcrete was sprayed onto the core box to take specimens for pH testing, and the pH test was performed. The results are shown in Table 1.

[0037] <Materials used> Ordinary cement: Commercially available, Blaine value 3,200 cm 2 / g Blast furnace slag cement β: Blast furnace cement type B, blast furnace slag content 45%, Blaine value 3,600 cm 2 / g Fly ash b: JIS product, Type II, Blaine value 4,500 cm 2 / g · Finely ground blast furnace slag: Ground and classified blast furnace slag, with an average particle size of 10 μm or less Fly ash d: fine fly ash powder, classified fly ash, average particle size 10 μm or less Gypsum: anhydrous gypsum, Blaine value 5,000 cm 2 / g Hydroxycarboxylic acid: Citric acid, commercially available Alkali metal carbonate: sodium carbonate, commercially available Calcium aluminate: Amorphous material obtained by quenching heat treatment equivalent to C12A7, Blaine value 5,900 cm 2 / g, containing 3 parts SiO2 in oxide equivalent Alums: Burnt alum, commercially available products Calcium hydroxide: commercially available Accelerator A: A mixture of 100 parts of calcium aluminate containing 3 parts of SiO2 in oxide equivalent, 10 parts of alum, and 3 parts of calcium hydroxide. Fine aggregate: Himekawa River sand from Itoigawa City, Niigata Prefecture, maximum dimension 5mm or less, density 2.62 Coarse aggregate: Niigata Prefecture Itoigawa No. 6 crushed stone, maximum dimension 15 mm, density 2.64

[0038] <Measurement method> Presence or absence of pipe blockage: After the spray test was completed, the spray nozzle was removed and the inside of the pipe was visually observed. Compressive strength: The compressive strength after 10 minutes was determined by a pull-out test. The pull-out formwork surface was covered with quick-setting sprayed cement concrete from the pin to the pin, and the pin was pulled out from the back of the formwork. The pull-out strength was then measured and calculated using the formula: Compressive strength = Pull-out strength x 4 / (contact area of ​​specimen). - Calcium hydroxide content: The concrete sprayed onto the core box was crushed and passed through a 74 μm sieve, and the result was measured using a differential thermal analyzer. pH: As with calcium hydroxide, the crushed sample and pure water were placed in a plastic container in a ratio of 1:20, and the test was performed with a stirrer rotating to prevent settling. 24 hours constitute one test, and the pH of the supernatant was measured. The sample was then filtered through filter paper, and the ratio of sample to pure water was adjusted to 1:20 again, and the test was repeated 50 times before being measured. ·Si ion amount: As with the pH measurement, the sample and pure water were placed in a plastic container in a ratio of 1:20, and the test was performed by rotating the stirrer to prevent settling. 24 hours constitutes one test, and the test for measuring the amount of Si ions in the supernatant was repeated 10 times, after which the measurement was made.

[0039] [Table 1]

[0040] From the results in Table 1, it was confirmed that the examples of the present invention are spray materials that are excellent in short-term strength development, reduction in calcium hydroxide amount, and low in Si ion elution. As comparative examples, in Experiments No. 1-9 to 1-14 in which ground granulated blast furnace slag and ground granulated fly ash were used, the amount of calcium hydroxide was high and the pH exceeded 11.

[0041] [Experimental Example 2] Using the same materials as in Experimental Example 1 and the same concrete as in Experiments No. 1-5, a spraying test was carried out by changing the types of blast furnace slag-containing cement, blast furnace slag, and fly ash. The results are shown in Table 2.

[0042] <Materials used> Blast furnace slag cement α: Blast furnace cement type A, slag content 20%, Blaine value 3,500 cm 2 / g Blast furnace slag cement γ: Blast furnace cement type C, slag content 65%, Blaine value 4,300 cm 2 / g Blast furnace slag A: crushed product, Blaine value 3,000 cm 2 / g Blast furnace slag B: crushed product, Blaine value 4,500 cm 2 / g Blast furnace slag C: crushed product, Blaine value 7,500 cm 2 / g Fly ash a: Blaine value 3,000 cm 2 / g Fly ash c: Blaine value 7,500 cm 2 / g

[0043] [Table 2]

[0044] From the results in Table 2, it was confirmed that good workability and good early strength development can be obtained by using the blast furnace slag-containing cement, blast furnace slag, and fly ash used in the present invention.

[0045] [Experimental Example 3] The same materials as in Experimental Example 1 and the same concrete as in Experiments No. 1-5 were used, and the amount and composition of the high-strength admixture were changed to carry out a shotcrete test. The results are shown in Table 3.

[0046] <Test Method> Slump test: Measure the slump immediately after concrete preparation and after 90 minutes. Strength test: A compressive strength test was conducted on specimens made of concrete sprayed into a core box and adjusted to dimensions of φ55mm x 110mm.

[0047] [Table 3]

[0048] From the results in Table 3, it was confirmed that the use of the high-strength admixture of the present invention provides excellent fluidity development and retention, excellent quick-setting properties, and good strength development. Experiment No. 3-7, which was conducted as a comparative example, showed poor results in both 1-day strength and 28-day strength, and Experiment No. 3-24 showed a low 28-day strength value, which is considered to be poor in long-term durability.

[0049] [Experimental Example 4] The amount of the accelerator added was 12 parts per 100 parts of cement material consisting of blast furnace slag-containing cement and fly ash, and mortar tests were carried out using calcium aluminate containing different amounts of SiO2. Each quick-setting agent was prepared by mixing 100 parts of calcium aluminate with 10 parts of alum and 3 parts of calcium hydroxide. The ratio of sand was 200 parts per 100 parts of cement material, the ratio of blast furnace slag-containing cement β:fly ash b was 100:100 parts, and mortar was prepared by adding 12 parts of high-strength admixture and 45 parts of water per 100 parts of cement material in the same manner as in Experimental Example 1. The results are shown in Table 4.

[0050] <Materials used> Accelerator A-1: ​​Amorphous material obtained by quenching heat treatment corresponding to C12A7, Blaine value 5,900 cm 2 / g, containing 0.5 parts of SiO2 in oxide equivalent Accelerator A-2: Amorphous material obtained by quenching heat treatment corresponding to C12A7, Blaine value 5,900 cm 2 / g, containing 1.0 parts of SiO2 in oxide equivalent Accelerator A-3: Amorphous material obtained by quenching heat treatment corresponding to C12A7, Blaine value 5,900 cm 2 / g, containing 2.0 parts of SiO2 in oxide equivalent Accelerator A-4: Amorphous material obtained by quenching heat treatment corresponding to C12A7, Blaine value 5,900 cm 2 / g, containing 4.0 parts of SiO2 in oxide equivalent Accelerator A-5: Amorphous material obtained by quenching heat treatment corresponding to C12A7, Blaine value 5,900 cm 2 / g, containing 5.0 parts of SiO2 in oxide equivalent

[0051] <Test Method> Setting test: In accordance with JIS R 5201-1997 "Physical test methods for cement", the setting time of mortar mixed with an accelerator was measured. Compressive strength: In accordance with JIS R 5201-1997 "Physical test methods for cement," the compressive strength of mortar to which an accelerator was added was measured 10 minutes and 3 hours after the accelerator was added.

[0052] [Table 4]

[0053] From the results in Table 4, it was confirmed that the use of the quick-setting admixture of the present invention provides excellent setting characteristics and good strength development. In Experiment No. 4-1, which was conducted as a reference example, the setting test started and ended at the same time, which prevented good adhesion when sprayed and may have caused blockage of the mixed area, and it was determined that this was not practical. In Experiment No. 4-6, which was conducted as a reference example, both the 10-minute and 3-hour compressive strengths were low, and it was determined that this was not practical.

[0054] [Experimental Example 5] Mortar tests were conducted by changing the mix ratio and amount of accelerator A added. A mortar was prepared using 200 parts of sand per 100 parts of cement material consisting of blast furnace slag-containing cement β and fly ash b, and a ratio of 100 parts of blast furnace slag-containing cement β:fly ash b:100 parts. As in Experimental Example 1, the high-strength admixture was used in an amount of 12 parts per 100 parts of the cement material, and water was used in an amount of 45 parts, and then a quick-setting admixture was added. As comparative examples, the same experiment was carried out using quick-setting adjuvants B and C. The results are shown in Table 5.

[0055] <Materials used> Accelerator B: A mixture of 100 parts of calcium aluminate containing 3 parts of SiO2 in oxide equivalent, 10 parts of alum, 1 part of alkali metal carbonate, and 100 parts of gypsum. Accelerator C: Calcium aluminate-based accelerator, commercially available

[0056] [Table 5]

[0057] From the results in Table 5, it was confirmed that the use of the quick-setting admixture of the present invention provides excellent setting characteristics and good strength development. For comparison, in Experiment No. 5-22, in which Accelerator B was used, the early strength was low, and in Experiment No. 5-23, in which Accelerator C was used, the early strength was very low and the strength at 28 days was also low.

[0058] [Experimental Example 6] Using the same materials as in Experimental Example 1, concrete was prepared in the same manner, and the unit amount of cement material consisting of blast furnace slag-containing cement and fly ash was set to 360 to 600 kg / m 3 The results are shown in Table 6.

[0059] <Materials used> Cement A: Cement made by mixing blast furnace slag-containing cement β and fly ash b in a mass ratio of 100:100 Cement B: Cement made by mixing ordinary cement, blast furnace slag C, and fly ash B in a mass ratio of 75:25:100 Cement C: Cement made by mixing ordinary cement, blast furnace slag C, and fly ash b in a mass ratio of 25:75:100 Cement D: Cement made by mixing ordinary cement and ground granulated blast furnace slag in a mass ratio of 100:30 Cement E: Cement made by mixing ordinary cement and fine fly ash powder in a mass ratio of 100:30

[0060] <Test Method> · Presence or absence of material separation: After the slump test, the slump plate was struck 15 times with a pounding rod to determine whether the mortar and aggregate separated.

[0061] [Table 6]

[0062] As can be seen from the results in Table 6, by mixing a specified amount of blast furnace slag-containing cement and fly ash according to the present invention, a spraying material was obtained that does not clog pipes due to quick-setting agents, has excellent early strength development, and has low calcium hydroxide content, pH, and Si ion leaching.

[0063] [Experimental Example 7] Except for changing the length of the mixing section after adding the accelerator, shotcrete was prepared with the same materials and mix as in Experiment No. 1-5 of Experimental Example 1, and accelerator A was added to the prepared shotcrete from the Y-shaped pipe. The piping was checked after spraying the quick-setting shotcrete for 10 minutes without changing anything except for the mixing section. A pull-out test was also conducted to check the mixability of the accelerator with the concrete. The measurement results are shown in Table 7. [Table 7]

Claims

1. A spraying material comprising a cement material consisting of blast furnace slag-containing cement and fly ash, a high-strength admixture, an accelerator, fine aggregate, coarse aggregate, and water, The high-strength admixture comprises gypsum and CaSO 4 0.5 to 5 parts by mass of an alkali metal carbonate and CaSO 4 and 0.2 to 5 parts by mass of oxycarboxylic acids per 100 parts by mass of the gypsum, The quick-setting admixture contains calcium aluminate, 1 to 20 parts by mass of an alum relative to 100 parts by mass of the calcium aluminate, and 1 to 20 parts by mass of calcium hydroxide relative to 100 parts by mass of the calcium aluminate, The content of the fly ash is 30 to 400 parts by mass per 100 parts by mass of the blast furnace slag-containing cement, The content of the high-strength admixture is 6 to 20 parts by mass per 100 parts by mass of the cement substance; The content of the quick-setting admixture is 6 to 20 parts by mass relative to 100 parts by mass of the cement substance, The content of the water is 30 to 55 parts by mass per 100 parts by mass of the cement substance; The spray material, wherein the alum is burnt alum.

2. The spraying material according to claim 1, wherein the blast furnace slag is 5 to 250 parts by mass per 100 parts by mass of the cement.

3. A spraying method using the spray material according to claim 1 or 2.

4. 4. The spraying method according to claim 3, comprising dry mixing a cement material consisting of blast furnace slag-containing cement and fly ash, fine aggregate, and coarse aggregate, then adding water and kneading the mixture, then adding a high-strength admixture, and further adding a quick-setting agent to prepare quick-setting sprayed concrete, and spraying the mixture.

Citation Information

Patent Citations

  • Spraying material and spray method using the same

    JP1997169557A

  • Spray material and spraying method using the same

    JP1998059760A

  • Spray material and spraying work

    JP1998287458A

  • Lightweight void filler and quick void filling method using the same

    JP1999100250A

  • Cement-based material for place for disposing of radioactive waste

    JP2000065992A